An Adaptive Handover Prediction Scheme for Seamless Mobility based-Wireless Networks - Sadiq, Ali Safa; Norshelia, Fisal; Ghafoor, Kayhan Zrar; Lloret, Jaime (Hindawi Publishing Corporation, 2014)
In this paper, we propose an Adaptive Handover Prediction scheme (AHP) for seamless mobility based wireless networks. That is, the AHP scheme incorporates fuzzy logic with AP prediction process in order to lend cognitive capability to handover decision making. Selection metrics, including received signal strength, mobile node relative direction towards the access points in the vicinity, and access point load, are collected and considered inputs of the fuzzy decision making system in order to select the best preferable AP around WLANs. The obtained handover decision which is based on the calculated quality cost using fuzzy inference system is also based on adaptable coefficients instead of fixed coefficients. In other words, the mean and the standard deviation of the normalized network prediction metrics of fuzzy inference system which are collected from available WLANs. Accordingly, they are applied as statistical information to adjust or adapt the coefficients of membership functions. In addition, we propose an adjustable weight vector concept for input metrics in order to cope with the continuous, unpredictable variation in their membership degrees. Furthermore, handover decisions are performed in each MN independently after knowing RSS, direction toward APs and AP load. Finally, performance evaluation of the proposed scheme shows its superiority compared with representatives of the prediction approaches.